Usulan Perbaikan Kinerja Mesin Produksi Kulkas Dengan Metode Overall Equipment Effectiveness Dan Failure Mode And Effect Analysis (PT. XYZ) - Prabu Hidayat, Trifenaus; Sugioko, Andre; Angelina, Cecilia (Metris: Jurnal Sains dan Teknologi, 2025)
PT XYZ is a company engaged in the household electronic equipment industry, one of which is refrigerator products. Two machines that are also responsible for the refrigerator production process are cold roll forming machines and PU injection machines. The refrigerator production process at PT XYZ is still considered ineffective because it does not reach the predetermined production target. The overall equipment effectiveness (OEE) method can assess the level of effectiveness of a machine based on three categories, namely availability, performance, and quality. Based on the results of calculating machine effectiveness using the OEE method, the two machines are below the ideal limit, namely 71.5% for the CRF machine and 57.22% for the injection machine, with a CRF machine performance value of 73.99% and 59.89% for the PU injection machine. An analysis of causes and solutions was carried out using the failure mode and effect analysis (FMEA) method using the risk priority number (RPN) assessment. The causes of low machine performance levels can provide solutions to improvements that must be made by the company. The recommended solution for the company is to apply preventive measures by adding UPS and generators to the factory, adding machine component damage detection sensors, and redesigning the jig.